هێمای دەروونی لە دەقەواڵاکانی شێرکۆ بێکەسدا (Sulaimani Journal for Humanities, 2021)
Psychic Symbols in Sherko Bekas's Long Poems. One of the skills and creativities in a poet's variable contemplations is his search, his depiction and his subconscious portrayal of his psychic state in poetry. This is done through discovering the hidden relations between the symbols and the symbolized. This similarization is a strong factor for the psychic annihilation the poets keep referring to. Therefore, this becomes a notable aperture through which scholars, researchers or readers can be familiar with the poet's emotional experience. What is meant by emotional experience is any experience that has caused a poet suffers anxiety and disquiet, such as emotional love, love for the land, for the nation, or for mankind and life in general. This type of symbol, psychic symbol, is an image projecting type, and they have a remarkable presence in creating psychic poetic images, which was especially common among the symbolists, they would interpret their anxiety and disquiet into poetic images, and insert them in the harmonious realm of language and poetry. The method of psychoanalysis has been used in this research, which in turn consists of two chapters. In the first one, the theoretical chapter, the relevant terms of symbols and symbolism in literature and psychology have been defined. The second chapter, which constitutes the practical one, sheds light on the psychic symbols in Sherko Bekas's long poems as well as their analyses. In the end, the conclusions and resources have been listed.
Keywords: symbol; psychic symbol; Sherko Bekas